Professional training of polish teachers of science and mathematical disciplines in the context of european integration - Yevtushenko, Natalia (Національний технічний університет "Харківський політехнічний інститут", 2023)
The article analyzes the issue of professional retraining of science and mathematics teachers in the Republic of Poland in the context of European integration processes. The development of the system of retraining and improvement of teacher's qualifications in the Republic of Poland under the influence of socio-political changes that took place in the country starting from the 90s of the XX century is being studied. The analysis of scientific and pedagogical sources regarding the state of retraining and improvement of teachers before the accession of Poland to the European Union was carried out. The regulatory and legal support of the educational process, including international regulations and documents, which became the basis for changes in the training of Polish teachers, was considered. The author described and analyzed modern forms of the organization of retraining of teachers of natural and mathematical subjects in postgraduate education of the country, offered by educational institutions in Poland. The form and content of retraining for teachers of science and mathematical subjects under the postgraduate education programme in the areas of "Pedagogical training" and "Teaching the next subject" were studied.

У статті проаналізовано питання професійної перепідготовки вчителів природничо-математичних предметів Республіки Польща в контексті євроінтеграційних процесів. Досліджено розвиток системи перепідготовки і вдосконалення вчителів Республіки Польща під впливом суспільно-політичних змін, які відбувалися в країні, починаючи з 90-х років ХХ століття. Проведено аналіз науково-педагогічних джерел щодо стану перепідготовки і вдосконалення вчителів до вступу Польщі в Європейській Союз. Розглянуто нормативно-правове забезпечення освітнього процесу, у тому числі міжнародні положення й документи, які стали основою для змін у питаннях підготовки польських учителів. Описано та проаналізовано сучасні форми організації перепідготовки вчителів природничо-математичних предметів у післядипломній освіті країни, що пропонуються освітніми закладами Польщі. Досліджено форми і зміст перепідготовки для вчителів природничо-математичних предметів за програмою післядипломної освіти в напрямах "Педагогічна підготовка" і "Викладання наступного предмета".
Професійна перепідготовка польських учителів природничо-математичних предметів у контексті європейської інтеграції
Keywords: teachers of natural and mathematical subjects; professional retraining of teachers; postgraduate education; the Republic of Poland; учителі природничо-математичних предметів; професійна перепідготовка вчителів; післядипломна освіта; Республіка Польща